2020
DOI: 10.3390/min10010065
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Precipitation of Carbonate and Phosphate Minerals Induced by the Bacterium Citrobacter freundii ZW123 in an Anaerobic Environment

Abstract: In this study, a facultative anaerobic strain isolated from marine sediments and identified as Citrobacter freundii, was used to induce the precipitation of carbonate and phosphate minerals in the laboratory under anaerobic conditions. This is the first time that the ability of C. freundii ZW123 to precipitate carbonate and phosphate minerals has been demonstrated. During the experiments, carbonic anhydrase, alkaline phosphatase and ammonium released by the bacteria not only promoted an increase in pH, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 90 publications
(157 reference statements)
1
8
0
Order By: Relevance
“…The O 1s peaks are closely aligned between HAP and struvite, as they centered around 531.6 eV in agreement with the literature values . Struvite contains ammonium ions leading to the N 1s XPS peak, which is centered around 401.8 eV, in agreement with previous reports . HAP and struvite contain Ca 2+ and Mg 2+ , respectively, with 2p peaks centered around 347.6 and 50.8 eV, respectively. ,, The P 2p region for HAP is centered around 133.8 eV, while struvite is at 134.0 eV. ,, The ratio of Ca/P in the HAP sample used in this study was found to be 1.14 via the XPS peak ratio of Ca 2p/P 2p, which is P-enriched compared to that of previous literature reports. , This Ca/P ratio is for the surface region as it is measured using XPS, while the bulk Ca/P may differ …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The O 1s peaks are closely aligned between HAP and struvite, as they centered around 531.6 eV in agreement with the literature values . Struvite contains ammonium ions leading to the N 1s XPS peak, which is centered around 401.8 eV, in agreement with previous reports . HAP and struvite contain Ca 2+ and Mg 2+ , respectively, with 2p peaks centered around 347.6 and 50.8 eV, respectively. ,, The P 2p region for HAP is centered around 133.8 eV, while struvite is at 134.0 eV. ,, The ratio of Ca/P in the HAP sample used in this study was found to be 1.14 via the XPS peak ratio of Ca 2p/P 2p, which is P-enriched compared to that of previous literature reports. , This Ca/P ratio is for the surface region as it is measured using XPS, while the bulk Ca/P may differ …”
Section: Resultssupporting
confidence: 90%
“…54,56,57 The P 2p region for HAP is centered around 133.8 eV, while struvite is at 134.0 eV. 54,55,57 The ratio of Ca/P in the HAP sample used in this study was found to be 1.14 via the XPS peak ratio of Ca 2p/P 2p, which is P-enriched compared to that of previous literature reports. 34,58 This Ca/P ratio is for the surface region as it is measured using XPS, while the bulk Ca/P may differ.…”
Section: ■ Materials and Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…Citrobacter and pseudomonas were the dominant strain at the beginning and end of the experiment, respectively. The function of formation of carbonates induced by Citrobacter was reported by previous literature [18]. Ma et al [39] injected Citrobacter into a bottle containing liquid medium.…”
Section: The Role Of Microbes In Chemical Composition Changes Of Pore Water and Carbonates Formationmentioning
confidence: 92%
“…The laboratory experiment related to authigenic carbonates, some study the formation duration of carbonate minerals under cold seep conditions [17], and some study the relationship between biominerals and the microbes [18]. However, there are few researches on the formation mechanism of carbonate minerals in marine sediments.…”
Section: Introductionmentioning
confidence: 99%